Detection of Human Herpesviruses (HHVs) in Semen of Human Male Infertile Patients - CHEN, Mo; CAI, Li-Yi; KANNO, Naoko; KATO, Takako; LU, Jinxing; JIN, Fan; WANG, Honghua; SEKITA, Masayo; HIGUCHI, Masashi; YOSHIDA, Saishu; YAKO, Hideji; UEHARU, Hiroki; et al. (Journal of Reproduction and Development, 2013)
Recently we demonstrated an ectopic expression of the human herpesvirus 1 thymidine kinase (HHV1-TK) gene by functioning of an intrinsic endogenous promoter in the transgenic rat (TG-rat), suggesting that HHV1 infection in humans induces expression of the TK gene with the ectopic promoter in the testis and results in accumulation of HHV1-TK protein, triggering male infertility similar to that in the TG-rat. Hence, in this study, we started to investigate a relationship between infection of herpesvirus and human male infertility. Semen was donated by Chinese male infertile patients (153 men, aged 21–49 years) with informed consent, followed by DNA preparation and analysis by PCR and DNA sequencing. Semen volume, sperm number and density, and sperm motility were examined. DNAs of HHV1, HHV4, HHV5 and HHV6 were confirmed by PCR, electrophoresis and DNA sequencing. Finally, virus DNA was identified in 59 patients (39%). The number of carriers was 39 (25%) for HHV1, 6 (4%) for HHV4, 33 (22%) for HHV5 and 3 (2%) for HHV6, respectively. Moreover, double-infection was found in 22 out of 59 specimens (37%), most of which were double-infection of HHV1 and HHV5 (15 out of 22 carriers). Though slight severity was present in some of the carriers, the relationship between virus infection and sperm impairment was not conclusive. Accordingly, it is essential to examine whether the viral HHV1-TK gene is expressed in the testis of the infertile human HHV carrier.